(untitled) (The Review of Diabetic Studies, 2025)
Background: Type 2 diabetes mellitus (T2DM) predisposes to subclinical cardiovascular abnormalities, even in the absence of overt cardiac disease. Electrocardiography (ECG) is a simple, non-invasive tool to detect early changes that may indicate silent cardiovascular risk. Objective: To evaluate the prevalence and pattern of ECG changes in T2DM patients without previously diagnosed cardiac disease and to identify predictors of such abnormalities. Methods: A cross-sectional study was conducted on 200 patients with T2DM attending four different tertiary care hospitals across India for period of one Year. Patients with known ischemic heart disease, heart failure, hypertension, or renal failure were excluded. Standard 12-lead ECGs were recorded and analyzed for abnormalities. Patients were stratified by duration of diabetes and glycemic control (HbA1c). Statistical analysis included Chi-square tests and multivariate logistic regression. Results: ECG abnormalities were observed in 88 patients (44%). Common findings included QTc prolongation (18%), ST-T changes (15%), left ventricular hypertrophy (8%), bundle branch block (5%), and resting tachycardia (4%). ECG changes were significantly more frequent in patients with diabetes duration >10 years (62% vs. 32%, p<0.01) and HbA1c ≥8% (57% vs. 28%, p<0.001). Logistic regression identified diabetes duration >10 years (OR 2.1; 95% CI 1.3-3.5; p=0.002) and HbA1c ≥8% (OR 2.6; 95% CI 1.5-4.4; p=0.001) as independent predictors of ECG abnormalities. Conclusion: Subclinical ECG changes are common in T2DM patients without overt cardiac disease, particularly in those with longer disease duration and poor glycemic control. Routine ECG screening may help detect early cardiovascular risk and enable timely intervention.